Implikasi Hukum Perkawinan Campuran WNI dan WNA Terhadap Status Kewarganegaraan Anak dibawah Umur (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
The research titled “Legal Implications of Mixed Marriages between Indonesian Citizens and Foreign Nationals on the Citizenship Status of Minors” discusses the legal consequences arising from marriages between Indonesian citizens (WNI) and foreign nationals (WNA), particularly regarding the determination of the citizenship status of minors. Mixed marriages often create legal complexities due to differences in citizenship systems between countries, which affect the rights and legal standing of children. The research problems focus on two main issues: how Indonesian positive law regulates the citizenship status of children born from mixed marriages, and how the state provides legal protection for such children. This study employs a normative legal research method with a statutory approach, analyzing relevant laws, doctrines, and court decisions. The results show that although Law Number 12 of 2006 on Indonesian Citizenship has improved the previous system by recognizing limited dual citizenship for children, its implementation still faces several obstacles. Complicated bureaucracy, a lack of understanding among officials, and persistent discriminatory practices remain major challenges. Therefore, it is necessary to reform the legal framework and administrative system of citizenship management to ensure that the principles of non-discrimination and the best interests of the child are effectively and fairly realized.